固体地球と氷床の相互作用 - 福田, 洋一; 西島, 潤; 風間, 卓仁; 中村, 和樹; 土井, 浩一郎; 菅沼, 悠介; 奥野, 淳一; 新谷, 昌人; 金田, 平太郎; 青山, 雄一; 三浦, 英樹; Yoichi, Fukuda; et al. (2017)
第8回極域科学シンポジウム/個別セッション：[OG] 極域地圏 12月5日（火）国立極地研究所 3階セミナー室 The Eighth Symposium on Polar Science/Ordinary sessions: [OG] Polar Geosciences Tue. 5 Dec./3F Seminar room, National Institute of Polar Research conference object